Optimal Operation Model of Vehicle to Vehicle Charging System - Revankar Swapnil R.; Kalkhambkar Vaiju N. (Journal of Electrical and Electronics Engineering, 2022)
Electric Vehicles (EVs) are believed to be a resolution to control global warming problems. Grid integration of EVs has become a prominent area of numerous research works. Vehicle to grid (V2G) and vehicle to vehicle (V2V) are the energy transfer methods that EVs can provide to increase the reliability and flexibility of the grid operation. In this paper, an incentive-based model of V2V power exchange between EVs is developed. EVs with surplus energy in their batteries can sell it to other EVs with a suitable amount. Buyers can buy the energy directly from the grid or they can buy from other EVs at a lower price (V2V approach). Aggregator collects information from vehicles located in the neighboring area at the realtime processes this energy transfer. Results show that this model decreases the energy cost to be paid by EV users to the grid. Further, provide profit for seller vehicles. To solve the proposed work DICOPT solver is used with a mixed-integer non-linear program (MINLP) in General Algebraic Modeling System (GAMS).